Pelatihan Penerapan Enkripsi pada Source Code dan Database: Meningkatkan Keamanan dalam Pengelolaan Aplikasi Web: Training on the Implementation of Encryption in Source Code and Databases: Enhancing Security in Web Application Management - Ahmad Sahal; Andre Kussuma Adiputra; Farida Nur Aini; Indra Listiawan; Rahagi Andhika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Web application security is a critical aspect of information system management, particularly in protecting data from cyber threats. One effective approach to enhancing security is the implementation of encryption in both source code and databases. This community service program aims to improve the knowledge and skills of teachers and students from the Software Engineering department at SMK Ibu Pawiyatan Tamansiswa Yogyakarta in applying encryption techniques in web application development. The implementation methods include theoretical training, hands-on practice, and case studies covering the use of encryption algorithms such as AES, RSA, and SHA-256 hashing, as well as PHP CodeIgniter 3 and MySQL. The selection of the CodeIgniter 3 framework is based on its alignment with the partner school's curriculum and its ease of use for beginner-level participants. The results of the program indicate significant improvements, including an increase in understanding of web application security concepts from 45% to 85%, knowledge of encryption functions from 40% to 90%, ability to implement encryption in source code from 30% to 80%, and database encryption skills from 25% to 75%. Additionally, participants’ perceived difficulty in implementing web application security decreased from 70% to 25%. This program produced training modules and technical documentation that can be utilized as sustainable teaching materials within the school environment. Therefore, the training not only enhances participants’ competencies but also supports the integration of web application security practices into a continuous learning process.